ANAK YANG TEREKSPLOITASI SEKSUAL DI DUNIA DARING: SEBUAH TINJAUAN SOSIOLOGI HUKUM - Cornella, Yohanna Septinita Alma; Zubaedah, Rahmi (Peneliti.net, 2024)
Social relations in a networked society change our current relationships. In a networked society where many lives are in the online world, social relations have an impact on children's vulnerability. Children in their relationship with the online world are vulnerable to becoming victims of sexual exploitation. This research explores the sexual exploitation of children in the online world due to low legal awareness. In this study, one case focused on children who were sexually exploited online. Data collection techniques are carried out by taking cases through kompas.id. By analyzing case studies, the research results show that sexual exploitation of children occurs due to a lack of legal awareness in society. The lack of legal knowledge and understanding of parents and schools shows that they do not know and understand the protection of children from the dangers of sexual exploitation in the online world. Due to the lack of knowledge and understanding of community law, the attitude and behavior of the community (schools) does not care for children. This was experienced in the case of E's son who was studying at a vocational school in Papua. Parents and the school community do not know how to protect their children from threats from online relationships. This has an impact on the attitude and behavior of those who do not accept or are aware of the legal protection of their children. The behavior of the school community tends to blame child victims of sexual exploitation in the online world. After all, children are victims. Meanwhile, the real perpetrators are still roaming the online world because they have not been caught and sentenced. This also shows that the state is weak in guaranteeing child protection.